Дмитро Прокопович Трощинський (1749–1829) – державний діяч Російської імперії, меценат української культури - Міронова, І.С. (Історичний архів. Наукові студії, 2015)
У статті розглянуто життєвий шлях державного діяча Російської імперії, українця за походженням, Дмитра Трощинського. Досліджено його походження, родовід, державну службу за часів правління Катерини ІІ, Павла І та Олександра І. Висвітлено родинні зв’язки Д. Трощинського із сім’єю Гоголів. Обґрунтовується висновок про те, що своєю діяльністю він сприяв пробудженню української культури та національної самосвідомості. В статье рассмотрены жизненный путь государственного деятеля Российской империи, украинца по происхождению, Дмитрия Трощинского. Исследованы его происхождение, родословная, государственная служба во времена правления Екатерины II, Павла I и Александра I. Освещены семейные связи Д. Трощинского с семьей Гоголів. Обосновывается вывод о том, что своей деятельностью он способствовал пробуждению украинской культуры и национального самосознания. The article describes the life of the great statesman of the Russian Empire, hwo had Ukrainian origin, the general procurator, chairman of the Postal Board, Privy Councillor, Senator, patron of Ukrainian culture, the owner of a home theater Dmitry Prokofyevich Troshchinsky. The questions of his origin, ancestry, public service, the ups and downs in his career during the reign of three imperators – Catherine II, Paul I and Alexander I are examined.
The author pays his attention to the quastions of Troshchinsky’ home education, youth years of his life, military service during the Russin-Turkish War of 1768–1774., as well as official and friendly relations with famous political, military and cultural figures of the Russian Empire – prince Mikhail Repnin, earl A. Bezborodko commander Mikhail Kutuzov, decembrists brothers Ants-Apostles, M. Bestuzhev-Rumin and others.
The article highlights the way of receiving by Troshchinsky the high state awards for his faithful service on the Russian Empire, the author suggestes the probability of his involvement in the conspiracy against the Emperor Paul I, highlights the last years of Troshchinsky in the estate Kybyntsi. A special place is given to the family ties of Troshchinsky with the M. Gogol family, his participation in the life of the famous ukrainian writer.
Considerable attention the author focuses on the role of the public figure in the development of Ukrainian science and culture, creating a home theater and building a park culture in his estate in Kaharlyk. The article substantiates the conclusion that D. Troshchinsky by his activities in Ukraine contributed awakening Ukrainian national consciousness.